2013
DOI: 10.1016/j.bjid.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic similarity of Burkholderia cenocepacia from cystic fibrosis patients

Abstract: Burkholderia cenocepacia may cause serious infections in patients with cystic fibrosis, and this microorganism can be highly transmissible. Pulsed-field gel electrophoresis is widely used to study the dynamics of strain spread in cystic fibrosis patients. The aim of this work was to perform pulsed-field gel electrophoresis-based molecular typing of B. cenocepacia isolates to evaluate the epidemiology of this species at our hospital. A total of 28 isolates from 23 cystic fibrosis patients were analyzed. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…CF patients infected with genotypically similar Burkholderia strains can have drastically different clinical outcomes. While useful for tracking Bcc epidemics, current genotyping methods-such as pulse-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and PCR-based methods with randomly amplified polymorphic DNA (RAPD) or BOX-PCR (Govan et al 1993;Jones et al 2004) -are not sufficient to define the scope of genetic diversity in infectious B. cenocepacia strains or to identify the underlying genetic differences responsible for variation in bacterial phenotypes that influence clinical outcomes (Mahenthiralingam et al 2000;Speert et al 2002a;Vonberg et al 2006;Pretto et al 2013). These low-resolution genotyping methods have shown that long-term sequential isolates from one patient typically belong to the same clonal type but nevertheless show phenotypic diversity (Cunha et al 2003;Coutinho et al 2011a,b).…”
mentioning
confidence: 99%
“…CF patients infected with genotypically similar Burkholderia strains can have drastically different clinical outcomes. While useful for tracking Bcc epidemics, current genotyping methods-such as pulse-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and PCR-based methods with randomly amplified polymorphic DNA (RAPD) or BOX-PCR (Govan et al 1993;Jones et al 2004) -are not sufficient to define the scope of genetic diversity in infectious B. cenocepacia strains or to identify the underlying genetic differences responsible for variation in bacterial phenotypes that influence clinical outcomes (Mahenthiralingam et al 2000;Speert et al 2002a;Vonberg et al 2006;Pretto et al 2013). These low-resolution genotyping methods have shown that long-term sequential isolates from one patient typically belong to the same clonal type but nevertheless show phenotypic diversity (Cunha et al 2003;Coutinho et al 2011a,b).…”
mentioning
confidence: 99%
“…By using recA gene sequence analysis and multilocus sequence typing, B. cenocepacia may be subdivided into four phylogenetic clusters, IIIA to IIID [7]. However, almost all clinically relevant isolates belong to the IIIA and IIIB groups [8, 9]. Epidemiological studies showed that strains ET-12 and several other epidemic dominant in Canada and Europe are part of the IIIA subgroup [10].…”
Section: Introductionmentioning
confidence: 99%